Эффективный численный метод определения динамических характеристик трубчатых теплообменных аппаратов - Шевелев, Александр Александрович; Тарасенко, Александр Николаевич (НТУ "ХПИ", 2009)
In the basis of modification of non-obvious method of hurrying account the method of calculation of unstationary processes of tubular heat-exchange vehicles is developed with cross motion of heat-carrying agent. The results of researches of dynamic descriptions of tubular air heater industrial boiler, got on the developed method, are presented in the article. Results showed that in the transitional processes of air heater and the transporting delay and curves of acceleration is absent is determined only heat-exchange and heat capacity of pipes of vehicle and heat-carrying agent.
Keywords: автоматическое управление; тепловые системы; движение теплоносителей